Urgensi Pendidikan Multikultural Indonesia dalam Menjaga NKRI - Hidayati, Isnani (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2020)
In some countries, multicultural education is always closely linked to important phases of democracy in people's lives. Democracy is based on the recognition of human rights not to implicitly discriminate against one's skin color, gender or culture. Everyone certainly has the same right to be treated as a right with responsibilities in accordance with their capabilities. In Indonesia itself, various multicultural education studies are a step that is being attempted to introduce special meaning in studying a plurality of people in Indonesia. So in this case, every part of society needs to respect each other's identity and be willing not to impose their own point of view about something that thinks is good, and is also forced upon others based on the standards that apply to it. If this can be realized, then multicultural education which is a learning process can lead the knowledge and value in society will be better implemented. Multricultural awareness in traveling is the spearhead of the future success of the Indonesian nation. Likewise with national identity, national integration, and placing religion as the foundation of the unity of a national principle is another part that is certainly inseparable from a state consciousness in a country of multiculturalism.